Evaluation of Functional Outcomes of Anterior Cruciate Ligament Reconstruction with Hamstring Autograft - Mansi Jitendra Patel; Jaysinh Shambhu Cauhan; Lalit Bambhaniya; Tejas Jogi; Utkarsh Panchal; Aakash Koladiya; Neel Bhavsar (Journal of Orthopedic and Spine Trauma)
INTRODUCTION: Anterior cruciate ligament is an intra-articular, extra synovial structure present in the central complex of the knee joint which along with other structures in the knee joint controls, limits motion and maintains static and dynamic equilibrium of knee joint. The knee joint is the most commonly injured of all joints and the anterior cruciate ligament is the most commonly injured ligament. The most commonly used grafts are hamstring graft and bone patellar tendon bone graft. In this study we are highlighting anatomical anterior cruciate ligament reconstruction by hamstring autograft. This study was undertaken to evaluate the results of arthroscopic anatomical anterior cruciate ligament reconstruction with hamstring graft using lysholm knee scoring scale. METHODS: This is the study of 40 cases of arthroscopic anterior cruciate ligament reconstruction using hamstring autograft in our institute with minimum follow up of 6 months. RESULTS: Results in this study are calculated according to lysholm knee score. 55% patients showed excellent results, 40% patients showed good results and 5% patients showed fair results. Average lysholm score is 90 in 40 patients. CONCLUSION: Anatomical anterior cruciate ligament reconstruction using hamstring graft technique has yielded excellent to good results in almost all patients with minimal complication and provides stable knees.